2015
DOI: 10.1016/j.celrep.2015.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils Regulate Humoral Autoimmunity by Restricting Interferon-γ Production via the Generation of Reactive Oxygen Species

Abstract: Summary Here we examine the mechanism by which plasmacytoid dendritic cells (pDCs) and type I interferons promote humoral autoimmunity. In an amyloid-induced experimental autoimmune model, neutrophil depletion enhanced anti-nuclear antibody development, which correlated with heightened IFN-γ production by natural killer (NK) cells. IFN-α/β produced by pDCs activated NK cells via IL-15 induction. Neutrophils released reactive oxygen species (ROS), which negatively modulated the levels of IL-15 thereby inhibitin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 56 publications
1
29
0
Order By: Relevance
“…Although neutrophils have been shown to act in an immunosuppressive capacity during chronic inflammatory conditions such as malignancy or viral infection, the possibility that a pro-resolving or protective neutrophil is present in lupus has only recently been proposed (15, 16, 3639). In an amyloid-induced lupus model neutrophil depletion worsened disease similar to our findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although neutrophils have been shown to act in an immunosuppressive capacity during chronic inflammatory conditions such as malignancy or viral infection, the possibility that a pro-resolving or protective neutrophil is present in lupus has only recently been proposed (15, 16, 3639). In an amyloid-induced lupus model neutrophil depletion worsened disease similar to our findings.…”
Section: Discussionmentioning
confidence: 99%
“…In an amyloid-induced lupus model neutrophil depletion worsened disease similar to our findings. A regulatory effect for neutrophils was suggested to be mediated by ROS inhibition of NK cell IFNγ production at local sites of inflammation (15). Another study demonstrated that Gr-1 hi CD11b + splenocytes suppress lupus pathogenesis in young male but not female NZB/W mice based on the finding that administration of anti-Gr-1 antibody in vivo increased anti-dsDNA antibody titers (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most direct experimental evidence of a role for neutrophils in driving systemic autoimmunity comes from chronic neutrophil depletion experiments [13, 14]. Coquery et al found that neutrophil depletion, achieved by every other day injection of the anti-Ly6G depleting mAb for four weeks, led to a reduction in auto-antibody titers, serum IFNγ, serum BAFF, T cell activation as well as the number of splenic germinal center B cells and plasma cells in the autoimmune prone B6.Fas lpr /J Tnfrsf17 −/− strain.…”
Section: Roles For Neutrophils In Classical Autoimmune Disease Modelsmentioning
confidence: 99%
“…The regulatory mechanisms utilized by neutrophils includes direct effects, via the production of cytokines such as IL-1, IL-6, IL-10 (in murine neutrophils only), TNF and BAFF that affect other immune cells, as well as indirect effects, through production of superoxides or consumption of nutrients (amino acids or even oxygen) that limit function of neighboring immune cells [13, 14]. Both stimulatory and inhibitory roles for neutrophils, based on their ability to produce various cytokines or indirectly affect other immune cells, have been described in a variety of autoimmune or autoinflammatory processes.…”
Section: Introductionmentioning
confidence: 99%